Tinjauan Hukum terhadap Tata Kelola Regulasi Pusat Layanan Berbasis Zakat di Malaysia sebagai Referensi Kebijakan bagi Indonesia - Muhsin Nor Paizin (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2026)
The demographic transition toward aging societies in Southeast Asia poses challenges to conventional welfare systems, compelling Islamic social finance institutions to evolve from mere cash aid distributors into providers of institutional care services. In response to this phenomenon, this study comprehensively examines how zakat-based social care homes in Malaysia navigate regulatory governance, analyzing civil legal frameworks, evaluating fund segregation architectures, and formulating compliance matrices. Employing a doctrinal legal research methodology, the study systematically analyzes regulations and case documents from model facilities such as Bait Al-Mawaddah and Darul Ilmi, covering the period from 1993 to 2025. The findings identify two key governance pillars: first, the need to implement a CAPEX/OPEX fund segregation model that synergizes waqf instruments for infrastructure with zakat for operational costs; and second, the requirement for a sequential bureaucratic compliance process that substantively operationalizes Maqasid Shariah principles regarding the preservation of life and dignity. This study contributes recommendations for formulating cross-institutional Standard Operating Procedures (SOPs) in Malaysia while offering an applicable reference for BAZNAS, LAZ, and the Indonesian Ministry of Social Affairs in regulating the governance of faith-based Social Welfare Institutions (LKS).